optimización del uso del espectro electromagnético para comunicaciones móviles mediante tecnologías mimo en redes de quinta generación” - Acurio Bustamante, Allisson Andrea (2024)
This study focuses on the optimization of the electromagnetic spectrum, a critical aspect in the era of exponential growth in data consumption and the proliferation of interconnected devices. The research is oriented towards the implementation of Multiple-Input Multiple-Output (MIMO) technology in mobile networks, particularly in high user density environments. This technology, fundamental in 5G networks, enables the simultaneous transmission of multiple data streams, significantly improving capacity, quality of service and user experience. To evaluate the performance of these technologies, advanced simulation tools and specialized software were used, particularly Matlab, a platform recognized for its advanced capabilities in modeling and simulation of 5G networks, has a 5G Toolbox. The research encompassed both the collection of numerical data on spectral performance and the analysis of the challenges and limitations inherent in the implementation of massive MIMO and adaptive MIMO technologies in 5G environments. This integrated approach provides a detailed understanding of the specific issues and potential solutions in the implementation of these advanced communication technologies.